2022
DOI: 10.5334/gh.1133
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Cardiology in South East Asia: Indonesian Lessons from the Present towards Improvement

Abstract: Although cardiovascular care has improved in the last decade in the low-and middleincome countries (LMICs) in South-East Asia Region; these countries, particularly Indonesia, are still encountering a number of challenges in providing standardized healthcare systems. This article aimed to highlight the current state of cardiology practices in primary and secondary care, including the novel cardiovascular risk factors, recommendations for improving the quality of care, and future directions of cardiovascular res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 50 publications
(81 reference statements)
0
14
0
Order By: Relevance
“…2 Scarcity of cardiologists in Indonesia was mentioned by Qanitha et al with a cardiologist and population ratio of 1:182.160, with 1485 cardiologists and 270 million people in Indonesia. 1 Despite the patient's routine control during her current pregnancy at a peripheral center with seven times antenatal care (ANC) with an obstetrician and cardiologist, the lack of standardization in healthcare providers and integration with central health care proves a sufficient number of ANC is still inadequate. Besides termination of pregnancy could be performed before she was referred or the disease progressed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Scarcity of cardiologists in Indonesia was mentioned by Qanitha et al with a cardiologist and population ratio of 1:182.160, with 1485 cardiologists and 270 million people in Indonesia. 1 Despite the patient's routine control during her current pregnancy at a peripheral center with seven times antenatal care (ANC) with an obstetrician and cardiologist, the lack of standardization in healthcare providers and integration with central health care proves a sufficient number of ANC is still inadequate. Besides termination of pregnancy could be performed before she was referred or the disease progressed.…”
Section: Discussionmentioning
confidence: 99%
“…As previously stated by Qanitha et al authority in decisionmaking, ignoring the guideline standards, and poor management of after-discharge care are mainly the problems of cardiovascular care in Indonesia. 1 Managing PH in pregnancy requires a multidisciplinary effort by a specialized Pregnancy Heart Team. A Pregnancy Heart Team is led by providers from a cardiologist, maternal-fetal medicine, obstetric anesthesia, pharmacy, and nursing to provide a holistic approach to patient care while facilitating opportunities for cross-disciplinary education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most LMICs in the Southeast Asian Region, especially Indonesia, only provide 24-hour rescue or primary PCI at the tertiary or national level. 6,8 A study in Jakarta, the capital of Indonesia, found that between 2007 and 2013, PCI procedures increased from 24% to 35%, and non-reperfusion patients decreased from 67ꞏ1% to 62ꞏ8%.…”
Section: Acs Treatment In Lmicmentioning
confidence: 99%
“…In this paper, we will describe the growth, number, ratio, and distribution of cath labs in Indonesia with the expectation of it providing a basis for policy-making. [4][5][6]…”
Section: Introductionmentioning
confidence: 99%